IMPLEMENTASI PROGRAM PERBIKAN GIZI MASYARAKAT KABUPATEN HULU SUNGAI UTARA UNTUK KATEGORI BALITA BERSTATUS GIZI KURANG (STUDI PADA KELURAHAN SUNGAI MALANG DAN KECAMATAN AMUNTAI SELATAN) - Norsanti, Norsanti; Affrian, Reno (Al Iidara Balad, 2019)
Based on Basic Health Research (RisKesDas) and Operation Weigh of Balita Kabupaten Hulu Sungai Utara, nutritional problem less increase during last three year, that is in 2015 Prevalence of less nutrition equal to 17,32%, 2016 Prevalence of less nutrition equal to 20,54% and in 2017 less nutrition Prevalence of 24% Prevalence of malnutrition less Hulu Sungai Utara District enter the categorization of public health problem because of the prevalence of nutrition less than 20%. Based on the mapping of malnutrition areas less malang river village 537 under-fives with less nutrition and South Amuntai 454 toddlers with less nutritional status.  Based on the result of the research that the implementation of the policy of nutrition improvement program of Hulu Sungai Utara Regency for under-five children category in Malang River Urban Village and South Amuntai Sub-district of Hulu Sungai Utara Regency has been running quite well, but in the implementation of this program there are still some obstacles between: 1. Lack of public knowledge about the importance of balanced nutrition for toddlers, 2. Patterns of Family Care, 3. Social Condition of the Community, and 4. There are still problems related to Interagency Coordination which runs the community nutrition improvement program, Factors that affect the implementation of nutrition improvement program the community for under-fives under-five category in Hulu Sungai Utara District study in southern Amuntai subdistrict and Malang River sub-district influenced by several factors: 1. Social Economics, 2. Pattern of Care, 3, Knowledge, Education and 4, Coordination Organizations